Meningkatkan Keterampilan Berbicara Peserta Didik Melalui Model Pembelajaran Role Playing Kelas VIII SMP Negeri 7 Palembang - Sapna Sapira; Novalia Novalia; Keni Apriliano; Hetilaniar Hetilaniar (JOURNAL SAINS STUDENT RESEARCH, 2024)
This study aims to improve students' speaking skills through the Role Playing learning model in class VIII.8 SMP Negeri 7 Palembang. This type of research is classroom action research (PTK) which uses quantitative data and is carried out in 2 (two) cycles. The subjects of this study were 36 students consisting of 15 boys and 21 girls. The data collection techniques used are observation (observation sheet), and tests (role play). Data analysis techniques were carried out descriptively qualitative and quantitative. The results of this study indicate that, the speaking skills of students after applying the Role Playing learning model at SMP Negeri 7 Palembang have increased from cycle I which obtained a percentage of 41%, the category is very lacking. Then experienced an increase in cycle II, which obtained a percentage of 86.11% in the good category.